A New Model for Caries Risk Prediction in Teenagers Using a Machine Learning Algorithm Based on Environmental and Genetic Factors - Pang, Liangyue; Wang, Ketian; Tao, Ye; Zhi, Qinghui; Zhang, Jianming; Lin, Huancai (Frontiers in Genetics, 2021)
Dental caries is a multifactorial disease, which can be caused by interactions between genetic and environmental risk factors. Despite the availability of caries risk assessment tools, caries risk prediction models incorporating new factors, such as human genetic markers, have not yet been reported. The aim of this study was to construct a new model for caries risk prediction in teenagers, based on environmental and genetic factors, using a machine learning algorithm. We performed a prospective longitudinal study of 1055 children (710 children for cohort 1 and 345 children for cohort 2) aged 13 years, of whom 953 (633 children for cohort 1 and 320 children for cohort 2) were followed for 21 months. All participants completed an oral health questionnaire, an oral examination, biological (salivary, and cariostate) tests, and single nucleotide polymorphism sequencing analysis. We constructed a caries risk prediction model based on these data using a random forest with an AUC of 0.78 in cohort 1(training cohort). We further verified the discrimination and calibration abilities of this caries risk prediction model using cohort 2. The AUC of the caries risk prediction model in cohort 2 (testing cohort) was 0.73, indicating high discrimination ability. Risk stratification revealed that our caries risk prediction model could accurately identify individuals at high and very high caries risk, but underestimated risks for individuals at low and very low caries risk. Thus, our caries risk prediction model has potential for use as a powerful community level tool to identify individuals at high caries risk.